The Limit of Tax Audit and Its Impact on the Status of Taxable Entities - Štieberová, Ivana (Public Governance, Administration and Finances Law Review, 2017)
Tax audit is a significant control mechanism nowadays, particularly in the context of increasing tax evasion and tax fraud. Taxable entities are obliged to tolerate the performing of tax audit for a certain statutory period. But what if the tax audit exceeds this statutory time limit? What impact does it have on the status of the taxable entity? Regarding the length of the tax audit, we will deal with the impact of the interest on value added tax refund on the status of the taxable entity. Will this interest contribute to its improvement?